Penerapan Metode Star Rating pada Evaluasi Keselamatan Jalan (Studi Kasus Ruas Jalan Frans Seda Kota Kupang) - Varda Marietta Adam; Imam Basuki (Jurnal Kridatama Sains dan Teknologi, 2026)
Road safety is an essential component of a sustainable transportation system. Kupang City, as the capital of East Nusa Tenggara Province, has experienced a significant increase in vehicle volume, which contributes to a higher risk of traffic accidents, particularly along Frans Seda Road. This study aims to evaluate the road safety risk level of this road segment using the International Road Assessment Programme (iRAP) methodology. The research employed a quantitative approach through direct field surveys, utilizing a 100-meter road segmentation technique. Each segment was assessed based on physical road safety parameters, including lane width, median condition, road surface quality, traffic signs and markings, lighting facilities, pedestrian crossings, and sidewalk availability. The collected data were processed using the iRAP system to generate the Star Rating Score (SRS), which is converted into a star rating scale (1–5) for each road user category. The results indicate that segments 22A and 22B obtained a 1-star rating for all road user types, indicating a very high risk level. After simulated infrastructure improvements, the rating increased to 3 and 4 stars, demonstrating a significant improvement in road safety conditions. These findings confirm that the iRAP method is effective for identifying road safety risks and provides a quantitative basis for evidence-based infrastructure improvement planning.